PENINGKATAN MOTIVASI BELAJAR IPA MELALUI STRATEGI PEMBELAJARAN JIGSAW PADA SISWA KELAS IVB SDN 01 NANGSRI KEBAKKRAMAT TAHUN 2015/2016 - Mawar Sari, Nur Indah Lailya (2016)
ABSTRACT IMPROVING SCIENCE LEARNING MOTIVATION TRHOUGH JIGSAW LEARNING STRATEGY On the FOURTH GRADE STUDENT Nur Indah Lailya Mawar Sari, A50120228, Primary Education Department, Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta, 2015. Abstract: This research aimed to improve students' learning motivation on science subject using jigsaw learning strategy. This classroom action research used qualitative descriptive. The subjects were teacher and students of class IVB in State Elementary 1 Nangsri, Kebakkramat. The collecting data using interview, observation, and documentation. The data validity used triangulation technique, contained data reduction, data presentation, deduction, and verification. The result gave the following data: asking activeness before the action was 4 students (17,39%), in cycle I was 10 students (43,48%). In cycle II was 19 students (82,61%). Students' attention to teacher explanation in learning process before the action was 6 students (26,09%), in cycle I was 13 students (56,52%). In cycle II was 23 students (100%). Students' enthusiastic on doing assignment before the action was 6 students (26,09%), in cycle I was 14 students (60,87%). In cycle II was 23 students (100%). Answerin teacher question before the action was 5 students (21,73%), in cycle I was 12 students (60,87%). In cycle II was 20 students (86,96%). In conclusion the implementation of jigsaw learning strategy could improve students'learning motivation on science subject of the class IVB in State Elementary 1 Nangsri, Kebakkramat, Karanganyar. Keywords: Learning strategy, Jigsaw, learning motivation